The role of economic intelligence in enhancing the monetary capacity of the Central Bank of Iraq (Japan as a model) - Rajaa jaber Abbas (Technium Business and Management, 2025)
Economic intelligence is an emerging, complex, and multidisciplinary field that has gained prominence in recent years, driven by the growing significance of the economy in shaping international relations. It has become a critical component in the operations of governments and central banks, with Japan’s experience serving as a notable example of its successful implementation. In Japan, monetary management has played a pivotal role not only in fostering financial and economic stability but also in benefiting society at large. This was achieved through strategic influence on interest rates and the stimulation of investments in both the public and private sectors. In stark contrast, the Iraqi economy has faced persistent financial and monetary instability, largely due to its heavy dependence on oil revenues as a source of foreign exchange. A key finding of this research highlights the importance of revitalizing monetary management by leveraging the exchange rate tool, which has historically been controlled through oil-derived foreign exchange revenues.